GVRG 2012 Research Study Survey: A Current Snapshot of Core Services - Hutchinson, Amy (Association of Biomolecular Resource Facilities, 2012)
As technology changes, the ability of core facilities to address the needs of their customers is critical to maintaining relevance in a competitive field. The Genomic Variation Research Group (GVRG), in conjunction with the DNA Sequencing (DSRG) and Nucleic Acids (NARG) research groups, has put together a comprehensive survey of the types of genomic technologies and their applications currently in place at core facilities. This survey will also serve as a guide for other genomic research groups on how to best serve the needs of the ABRF membership. The approximately 10-minute survey was sent out to the ABRF membership as well as the discussion group forum for respondents. The questions ranged from sample types utilized to usage percentages of certain applications including the latest sequencing platforms. As these new sequencing technologies have changed the landscape of tools available to researchers we sought to understand the impact on the platforms previously employed. The survey also includes high level project management questions and general demographic data. A survey of this nature is ideal as it seeks to capture a snapshot of the ever-changing world of laboratory technologies. Long-term tracking of trends in these areas will be crucial to core facilities of the future.